Signs of sensitivity and espionage in the Holy Quran Study and analysis - Abbood Hasan, Salam (International Journal of Psychosocial Rehabilitation, 2020)
Praise be to God, Lord of the worlds, and prayers and peace be upon the Messenger of God, may God bless him and grant him peace, and on his family and his righteous companions. And after: One of the masterpieces of the statement in the verses of the Noble Qur’an are the terms “espionage and sensitivity”, the difference between them is a point under “gym”, but the difference in meaning and significance between them is clear, even though the meaning appears close between the two terms in the Qur’anic usage very closely in terms of significance, where they share two meanings: research Recognition, invisibility and concealment. And they separate at one point under the "gym", which is the dominance of its use in evil. While sensitization is characterized by "distraction" by its victory in goodness, and sensitization in the Qur’an was mentioned once in Surat Yusuf in verse (87) as well as espionage mentioned once in Surat Al-Hujurat in verse (12) and from this standpoint the topic of research was selected ((verses of espionage and sensitivity in The Holy Quran is an analytical study)) To study the interpretation of these two terms, a detailed analytical study, as follows: the analysis of words, and I spoke about the occasion of the verse, the reason for the descent of the verse if any, the Qur’anic readings, the stopping and starting, the different expressions in it, the rhetoric and the Qur’anic sects mentioned in the verse, and the meaning The general verse, and the provisions of any verse that are used, through sources of interpretation, books of jurisprudence, morals, mysticism, and Quranic studies. Likewise, I did not know of scholars, commentators, or readers, nor did I mention the book card in the margin for fear of the high percentage of electronic induction. At the end of the research, a conclusion with the most important results reached, then a list of sources and references.